PERANAN SERIKAT BURUH SOLIDARITAS INDONES IA KOTA PEMATANGSIANTAR DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL DI KOTA PEMATANGSIANTAR DITINJAU DARI UNDANG-UNDANG NOMOR 21 TAHUN 2000 TENTANG SERIKAT PEKERJA/SERIKAT BURUH - Cresensia Yohana Saragih; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
This Research discussed about the role of the Labor Union Solidarity ofIndonesia in resolving disputes industrial relations in Pematangsiantar city. Theselection of this title based on that Labor Union Solidarity of Indonesia inPematangsiantar not effective in implementing up his role as parties in disputeresolution industrial relations through negotiations bipartite. In the implementationof the bipartite discussion have not been in accordance with article 3 paragraph 2 ofthe law number 2 year 2004 about industrial relations dispute resolution, so that theprotracted dispute resolution. In this case the Labor Union Solidarity of Indonesiapredicted by the workers to be able to fight for and their interests have not be able tokeep up his role well, as it is not consistent with the objectives of the formation oflabor union that is in article 4 paragraph ( 1 ) the act of number 21 year 2000regarding labor union , which is to provide some level of protection, the rights andinterests of the defense, as well as improve the welfare of that was appropriate forunion workers and their families. The purpose of writing this thesis; first, to know therole of the Labor Union Solidarity of Indonesia in resolving disputes industrialrelations in Pematangsiantar city, second, to know what obstacles faced by the LaborUnion Solidarity of Indonesia in resolving disputes industrial relations inPematangsiantar city, third, to know the efforts made by the Labor Union Solidarityof Indonesia to overcome obstacles of resolving conflicts industrial relations.This type of research can be classified in the type of sociological juridicalresearch. The Research was conducted at the office of Labor Union Solidarity ofIndonesia in Pematangsiantar City. Sociological law research uses primary data andsecondary data, while population and sample are the parties related to the problemstudied in this research. Technique of collecting data in this research by interviewand literature study. Second, the obstacles faced by SBSI Pematangsiantar City is thelow quality of human resources, lack of funds, lack of communication, as well asobstacles from the employers and the government, Third, the efforts undertaken bySBSI Pematangsiantar City isproviding education and training, raising funds,JOM Fakultas Hukum Universitas Riau Volume V Nomor 2 Oktober 2018 2improving communication and actively involved in the Tripartite CooperationInstitution.From the results of research problems there are three main things that canbe concluded. First, SBSI Pematangsiantar City has not been effective in resolvingindustrial relations disputes in Pematangsiantar City, Second, the obstacles faced bySBSI Pematangsiantar City is the low quality of human resources, lack of funds, lackof communication, as well as obstacles from the employers and the government.Writer suggestion, First, The parties prioritize the principle of deliberation toconsensus in resolving any industrial relations disputes that occur,Second, the Parties are expected to better understand their rights and obligationsrespectively. Third, It is hoped that both the government, academics and the widercommunity can cooperate in fighting for the rights of the oppressed workers.Key Words : Labor Union-Dispute-Industrial Relations